Variations of Thermal Properties with Water Content and Density of Residual and Basaltic Sands from Chile - Vasco-Calle, D (GEOLOGICAL SOC PUBL HOUSE, 2024)
Renewable energy has become a relevant alternative to solve energy and environmental problems worldwide. Characterization of geothermal resources is fundamental for an efficient and sustainable extraction of heat. In this study, thermal conductivity, lambda, volumetric heat capacity, C, and thermal diffusivity, alpha, of two soils from Chile, namely B & iacute;o B & iacute;o sand and Maicillo residual soil, were analysed. B & iacute;o B & iacute;o sand is a uniform and clean sand that mainly consists of basaltic particles, whereas Maicillo soil is a silty and clayey sand with a high quartz content. Samples were tested with a thermal needle probe at varying water contents and densities. Measurements to obtain lambda, C and alpha were undertaken. These results allowed the patterns and relationships between geotechnical and heat transfer parameters to be analysed. It was found that dry soil conditions led to the lowest values of lambda, while saturated soil conditions led to the highest values. Moreover, Maicillo soil has higher capabilities to transfer heat than B & iacute;o B & iacute;o sand, and can reach up to 50% greater lambda for dense soil and saturated conditions. This is due to its quarzitic and clayey mineralogy and non-uniform grain-size distribution. The results from this research represent an important contribution to industrial applications.